Fonologi Bahasa Nambla di Keerom Papua: Phonology of Nambla Language in Keerom Papua - Arman Arman (Balai Bahasa Provinsi Papua, 2020)
The research aims at describing phonological system of Nambla language in Dusun Nambla, specially: (1) the vowel system, (2) consonant system, (3) diphthong, (4) distribution of vowels and consonants, (5) form of syllables. The method applied in this research is descriptive method. The data was collected by using basic techniques such as ‘recording, participate, anda face to face” technique. From the analysis it is found that Nambla language has 27 phonemes. They are 6 vowels, 17 consonants, 4 diphthongs. Besides, it has 11 vowel sequences and 10 consonant cluster.